2018
DOI: 10.1177/0309364617698518
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the custom-mold room temperature vulcanizing silicone toe separator on hallux valgus

Abstract: A custom-mold room temperature vulcanizing silicone toe separator can decrease hallux valgus angle and pain with no serious complications. Clinical relevance The custom-mold room temperature vulcanizing silicone toe separator for treatment of hallux valgus reduces deformity and hallux pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 18 publications
0
44
0
3
Order By: Relevance
“…Eighty seven full texts were screened and 76 were excluded. Eleven studies were included in the final analysis [ 42 , 43 , 44 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. The identification process is shown by a flow diagram, which is in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighty seven full texts were screened and 76 were excluded. Eleven studies were included in the final analysis [ 42 , 43 , 44 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. The identification process is shown by a flow diagram, which is in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, mobilization and manipulation are often selected as treatment options or assistive treatment options. The results of two small preliminary studies suggest that graded mobilization and manipulation may improve pain and function in the short term, but further study of the long-term effects is needed [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…The static orthosis with a toe separator tested by Moulodi et al 38 also showed a significant positive HVA correction of 2.67° in the HV group (SMD: 0.75, 95% CI: 0.143 to 1.325). Chadchavalpanichaya et al 36 developed a custom-moulded room temperature vulcanising (RTV) toe separator, which helps to correct the HVA by 2.1° in the HV group (SMD: 0.41, 95% CI: −0.012 to 0.827). The pooled estimation for orthoses with a toe separator was further investigated that the effect is medium (SMD: 0.50, 95% CI: 0.189 to 0.803) with I 2 14.52%.…”
Section: Resultsmentioning
confidence: 99%
“…Among those, the application of foot and toe orthoses to correct the alignment of the first metatarsophalangeal joint is preferred for minor to moderately severe HVD [12,13]. However, previous studies on the effect of foot and toe orthoses in HVD have only verified relatively simple variables such as satisfaction with wearing a foot and toe orthosis or changes in the angle of the big toe spread [11][12][13]. Thus, verification of the effects of kinetic variables such as the ground reaction force (GRF) through three-dimensional (3D) gait analysis according to the various type of orthoses for HVD is lacking.…”
Section: Yong-wook Kimmentioning
confidence: 99%